Divination, Greece and Rome - Bonnechere, Pierre (The Encyclopedia of Ancient History, 2013)
Divination (Greek mantike, Latin divinatio) encompasses all forms of interrogating the gods. Contrary to general belief, its purpose is not merely to “know the future.” Confronted with any immediate choice entailing unknown repercussions, the consultant depends on divination in order to act effectively and be released from excessive anxiety, when too many hidden things remain inaccessible to his reason.

Human sacrifice, Greece and Rome - Bonnechere, Pierre (The Encyclopedia of Ancient History, 2013)
Human sacrifice is a bone of contention for historians. The concept is elusive: should we distinguish between the victim that is offered to specific gods (human sacrifice) and the one that is not (ritual murder)? This issue very often superimposes modern categories on ancient texts, in which such a distinction is never obvious. Would this distinction remain valid if human sacrifice belonged to representation rather than reality? Comparisons with other cultures remain particularly hazardous if the phenomenon has not been thoroughly studied for each of them.

Groves, sacred, Greece and Rome - Bonnechere, Pierre (The Encyclopedia of Ancient History, 2013)
The “sacred grove” (Greek alsos, plural alse; Latin lucus or nemus) is a difficult concept to define. Theoretically, it differs from wild wood, flower and vegetable garden, vineyard, and orchard. Yet the overlap among these concepts is such that precise distinction proves impossible. Since the definitions by late lexicographers rely more on deductive reasoning than on any real knowledge, their statements are inconclusive and sometimes in contradiction to concrete cases. Archaeological evidence has long been disappointing: landscaping has only recently attracted the attention of researchers, but many sanctuaries were excavated long ago. However, recent excavations seem promising.

Trophonios - Bonnechere, Pierre (The Encyclopedia of Ancient History, 2012)
The Boiotian Trophonios (god, hero, or daimon), had a manteion, oracular shrine, at Lebadeia, which was active from the archaic to the Roman period.